Can recombinant human thrombomodulin increase survival among patients with severe septic-induced disseminated intravascular coagulation: a single-centre, open-label, randomised controlled trial. Issue 12 (30th December 2016) - Hagiwara, Akiyoshi; Tanaka, Noriko; Uemura, Tatsuki; Matsuda, Wataru; Kimura, Akio
Abstract : Objective: To determine whether treatment with recombinant human thrombomodulin (rhTM) increases survival among patients with severe septic-induced disseminated intravascular coagulation (DIC). Design: Single-centre, open-label, randomised controlled trial. Setting: Single tertiary hospital. Participant: 92 patients with severe septic-induced DIC. Interventions: Patients with DIC scores ≥4, as defined by the Japanese Association of Acute Medicine, were diagnosed with DIC. The envelope method was used for randomisation. The treatment group (rhTM group, n=47) was intravenously treated with rhTM within 24 hours of admission (day 0), and the control group (n=45) did not receive any anticoagulants, except in cases of deep venous thrombosis and pulmonary embolism. Primary and secondary measurements: Data were collected on days 0 (admission), 1, 2, 3, 5, 7 and 10. The primary outcome was survival at 28 and 90 days. The secondary end points comprised changes in DIC scores, platelet counts, d -dimer, antithrombin III and C reactive protein levels, and Sequential Organ Failure Assessment (SOFA) scores. All analyses were conducted on an intent-to-treat basis. Main results: The 28-day survival rates were 84% and 83% in the control and rhTM groups, respectively (p=0.745, log-rank test). The 90-day survival rates were 73% and 72% in the control and rhTM groups, respectively (p=0.94, log-rank test). Meanwhile, the rates of recovery from DIC (<4) were significantly higher in the rhTM group than in the control group (p=0.001, log-rank test). Relative change from baseline of d -dimer levels was significantly lower in the rhTM group than in the control group, on days 3 and 5. Conclusions: rhTM treatment decreased d -dimer levels and facilitated DIC recovery in patients with severe septic-induced DIC. However, the treatment did not improve survival in this cohort. Trial registration number: UMIN000008339.